2003
DOI: 10.1152/ajpheart.00893.2002
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory sinus arrhythmia is associated with efficiency of pulmonary gas exchange in healthy humans

Abstract: . Respiratory sinus arrhythmia is associated with efficiency of pulmonary gas exchange in healthy humans. Am J Physiol Heart Circ Physiol 284: H1585-H1591, 2003. First published January 23, 2003 10.1152/ajpheart.00893.2002.-Respiratory sinus arrhythmia (RSA) may be associated with improved efficiency of pulmonary gas exchange by matching ventilation to perfusion within each respiratory cycle. Respiration rate, tidal volume, minute ventilation (V E), exhaled carbon dioxide (V CO2), oxygen consumption (V O2), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
103
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 29 publications
(36 reference statements)
9
103
0
7
Order By: Relevance
“…Data shown are from a male (28 years) and the mean heart rate was 53 beats min -1 with HF and LF components of 56.8 NU and 39.1 NU respectively, when supine. During HUT, the mean heart rate was 86 beats min -1 with HF and LF components of 28.6 NU and 63.4 NU respectively J Physiol Sci (2009) 59: 31-36 33 ventilation, as shown by others [23][24][25][26][27]. Also, in the current study, a decrease in HF cardiac variability was shown with HUT, again similar to the findings of others [14,[18][19][20]33].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Data shown are from a male (28 years) and the mean heart rate was 53 beats min -1 with HF and LF components of 56.8 NU and 39.1 NU respectively, when supine. During HUT, the mean heart rate was 86 beats min -1 with HF and LF components of 28.6 NU and 63.4 NU respectively J Physiol Sci (2009) 59: 31-36 33 ventilation, as shown by others [23][24][25][26][27]. Also, in the current study, a decrease in HF cardiac variability was shown with HUT, again similar to the findings of others [14,[18][19][20]33].…”
Section: Discussionsupporting
confidence: 91%
“…Others [5] reported that during HUT, tidal volume was slightly lower when ventilation was controlled with a metronome (0.33 Hz), and this resulted in no accompanying changes in transcutaneous P CO 2 . An improvement in alveolar gas exchange efficiency may have contributed to the lowering of PET CO 2 with HUT in the study by Cooke et al [14], but this would suggest an increase in respiratory sinus arrhythmia [26,36] and a concomitant increase in the HF component of HRV. However, Cooke et al [14] reported a decrease in HRV at respiratory frequency with head-up tilt, consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We could demonstrate an increase in alveolar dead space accompanied by a decrease in RSA magnitude. Giardino et al (2003) magnitude was positively associated with pulmonary gas exchange efficiency, measured as the average ventilatory equivalent of CO 2 and O 2 , in humans, and concluded that RSA might improve the efficiency of pulmonary gas exchange.…”
Section: Et Al 2003) Regarding Cardiac Phasic Vagal Activitymentioning
confidence: 98%
“…This 'theory' has important clinical applications, and may partly account for the association between low RSA and a variety of cardiovascular/cardiopulmonary risk factors and disease processes (see references in the article by Sin et al 2010). Nevertheless, while the pioneering demonstrations in dogs (Hayano et al 1996) and humans (Giardino et al 2003) were appealing, recent findings by Tzeng, Galletly, Larsen and co-workers came, with time, to question Hayano's views (e.g. Tzeng et al 2007Tzeng et al , 2009).…”
mentioning
confidence: 99%